Aprendizagem no cotidiano escolar: direitos, experiências e percepções discentes - Lemons, Caroline Caldas (My University, 2020)
This thesis had as global aim, through narratives about student experiences, to establish possible connections among the Cultures of Pedagogical Intervention (of reproduction, recommendation, discipline, grant/transference and emancipation) and the promotion of learning; and, from there, to propose possibilities of pedagogical interventions aimed at actualisation of the right to learning. The fragilities that accompany investigations on student learning experiences, the lack of literature in this regard and the comprehensive deficit surrounding the learning that takes place in and from the school's daily life, specifically in the perception of school participants, comprise part of the justification for the development of this theoretical-empirical study. The cultural pedagogical interventions identified in a previous study based on oral and written narratives by teachers from Caxias do Sul’s Municipal School Network supported the dialogue between what was lived and what was perceived by students in the scope of Basic Education. The knowledge developed around student perceptions about school learning resulted from interpretations produced from the reflective narratives of thirty adolescents (that were studying in the last grade of Elementary School) in dialogue with the theoretical and methodological framework that supports this research. The construction of the students’ narratives followed the ethical, theoretical and methodological principles of the narrative interview discussed by Bertaux, Galvão and Botía, being analysed and interpreted bearing in mind the Discursive Textual Analysis, systematised by Moraes and Galiazzi, in dialogue with the principles of the Sociology of Everyday Life, themed by Pais. Through a qualitative approach, the research gathered the mentioned methodological procedures and the interpretative perspectives of Charlot, Dubet, Freire, Honneth, Lefebvre, McCowan, Shim, Stecanela, Vieira and Vigotsky, among others. As part of the investigative results, this thesis conveys learning that takes place through school experience, senses and meanings attributed by students to school, as well as students’ perceptions about the links between their contexts of school and non-school social interactions. In conclusion, it identifies positive human characteristics in the composition of the pedagogical relationship (respect, empathy, patience, good humor, humility, responsibility and creativity), conditioning elements of school learning (well-being, recognition, listening and choices, time and affection) and potential pedagogical interventions for learning. Thus, this thesis suggests the attention and strengthening of positive human characteristics and the conditioning elements of learning as the mainstay of the choice and adoption of potential pedagogical interventions for learning, characterised by the exploration of creativity and dynamization of teaching. Finally, the set above ratifies important issues to reinvigorate schooling and contributes to the reaffirmation of the right to learning.
Esta tese teve como objetivo geral, por meio de narrativas sobre as experiências estudantis, estabelecer possíveis conexões entre as Culturas de Intervenção Pedagógica (de reprodução, recomendação, disciplina, outorga/transferência e emancipação) e a promoção da aprendizagem e, a partir disso, propor possibilidades de intervenções pedagógicas com vistas à efetivação do direito à aprendizagem. As fragilidades que acompanham investigações sobre as experiências de aprendizagem estudantis, a carência de literatura a esse respeito e o déficit compreensivo em torno das aprendizagens que se processam no e a partir do cotidiano da escola, especificamente na percepção dos(as) sujeitos escolares, compõem parte da justificativa para o desenvolvimento deste estudo teórico-empírico. As intervenções pedagógicas culturais identificadas em estudo anterior a partir de narrativas orais e escritas de docentes da Rede Municipal de Ensino de Caxias do Sul subsidiaram o diálogo entre o vivido e o percebido pelos(as) discentes no âmbito da Educação Básica. O conhecimento elaborado em torno das percepções estudantis sobre as aprendizagens escolares decorreu das interpretações produzidas a partir das narrativas reflexivas de trinta adolescentes do último ano do Ensino Fundamental em diálogo com o referencial teórico-metodológico que subsidia esta pesquisa. A construção das narrativas estudantis seguiu os princípios éticos, teóricos e metodológicos da entrevista narrativa discutida por Bertaux, Galvão e Botía, sendo analisadas e interpretadas à luz da Análise Textual Discursiva, sistematizada por Moraes e Galiazzi, em diálogo com os princípios da Sociologia do Cotidiano, tematizada por Pais. De caráter qualitativo, a pesquisa reuniu aos procedimentos metodológicos mencionados as perspectivas interpretativas de Charlot, Dubet, Freire, Honneth, Lefebvre, McCowan, Shim, Stecanela, Vieira e Vigotsky, dentre outros. Como parte dos resultados investigativos, esta tese expressa aprendizagens que se processam pela experiência escolar, sentidos e significados atribuídos pelos(as) estudantes à escola, assim como percepções estudantis sobre os vínculos entre os seus contextos de interações sociais escolares e não escolares. A título de conclusão, identifica características humanas positivas na composição da relação pedagógica (respeito, empatia, paciência, bom humor, humildade, responsabilidade e criatividade), elementos condicionantes da aprendizagem escolar (bem-estar, reconhecimento, escutas e escolhas, tempo e afeto) e intervenções pedagógicas potenciais à aprendizagem. Posto isto, esta tese sugere a atenção e o fortalecimento das características humanas positivas e dos elementos condicionantes da aprendizagem como esteio a escolha e a adoção de intervenções pedagógicas potenciais à aprendizagem, caracterizadas pela exploração da criatividade e dinamização do ensino. Por fim, o conjunto acima ratifica questões importantes para revigorar a escolarização e contribui para a reafirmação do direito à aprendizagem.
Keywords: Aprendizagem; Educação básica; Educação; Learning; Basic Education; Education